Using a Multiple-Schedule Procedure to Signal the Availability of Attention: Three Demonstrations. Issue 4 (July 2020) - Niedfeld, Amanda; Rapp, John T.; Coon, Jodi C.; Cook, Jennifer L.
Adjudicated adolescents detained in residential facilities for illegal sexual behavior, as well as adolescents living at home, may engage in problem behaviors such as excessive vocalizations. In residential detention facilities, these excessive vocalizations may result in disciplinary action and loss of privileges. Moreover, excessive vocalizations may also reduce the amount of positive social interactions that staff members and caregivers have with the adolescents. The current study evaluated a multiple-schedule procedure for reducing excessive vocalizations displayed by three adolescents. The procedure involved (a) a red card to signal that attention was not available and (b) either a green card or no card to signal that attention was available. Results show that the participants learned to abstain from vocalizing for up to 30 min when a caregiver presented the red card. In addition, the treatment effects persisted during generalization assessment sessions.